Sistem Informasi Booking Wedding Organizer Berbasis Website pada Max Entertaiment Kudus - Sindhi Diah Ayu Palupi; Magdalena A. Ineke Pakereng (KITA Institute, 2023)
Wedding organizers are services that can assist in preparing and carrying out wedding events. Max Entertainment is one of the providers of wedding organizer packages in Kudus whose services are still done manually. The problem that often arises is the lack of information that can be a guide for making decisions on wedding receptions and planning costs (budget) that must be incurred by the bride and groom. Therefore, the author designed an information on ordering wedding organizer services which aims to make it easier for the bride and groom to make the process of ordering wedding organizer services and become a promotional event for Max Entertainment Kudus itself. The method applied in this research is the UML method which is useful as a guide in designing this system and Black Box Testing as a method of testing the system that has been built. The expected result in this research is the creation of a website-based wedding organizer information system so that it can be accessed by prospective wedding organizer customers to place orders.